Treatment Outcome of Displaced Proximal Humeral Fractures with Joshi’s External Stabilization System: A Prospective Study - Karki, Prateek; Ranabhat, Roshani; Shrestha, Dinesh Kumar; KC, Dipendra; Sapkota, Suhail (Journal of Nepalgunj Medical College, 2022)
Introduction: Proximal humeral fracture accounts for four to five percentage of all fractures. Undisplaced fractures can be managed conservatively however, for displaced fractures; no particular method is a panacea. In our study we treated displaced proximal humeral fracture with Joshi’s external stabilizing system.Aims: To evaluate functional outcome of displaced proximal humerus fractures managed byJoshi’s external stabilizing system.Methods: This prospective study includedall patients with displaced proximal humerus fracture (Neer’s type two and three); treated with JESS from August 2018 to August 2021at Nepalgunj Medical College, Kohalupurand functional outcome was evaluated using Neer’s criteria at final follow-up. Ethical clearance was obtained from Institutional Review Committee.Results: A total of 40 patients, 23 males and 17 females with mean age of 41.2 years (range from 18 to 60) were included. Mean follow-up duration was 24 ± 1.7 weeks.  All fractures united at an average of 13 ± 1.7 weeks. Twenty-nine patients (72.5%) had an excellent result with average score of 92.7 ± 2.3 and remaining 11(27.5%) had satisfactory functional outcome with average score of 84.7 ± 1.7 according to Neer’s criteria. Three patients had bicipital tendonitis that resolved within eight weeks of implant removal while two had pin tract infection which resolved with oral antibiotics and dressing.Conclusion: Joshi’s external stabilizing system is an effective treatment option in patients with displaced proximal humeral fractures.